2019
DOI: 10.3390/toxins12010019
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the X Factor in Bacterial Pathogenesis: Association of orfX-p47 Gene Clusters with Toxin Genes in Clostridial and Non-Clostridial Bacterial Species

Abstract: The botulinum neurotoxin (BoNT) has been extensively researched over the years in regard to its structure, mode of action, and applications. Nevertheless, the biological roles of four proteins encoded from a number of BoNT gene clusters, i.e., OrfX1-3 and P47, are unknown. Here, we investigated the diversity of orfX-p47 gene clusters using in silico analytical tools. We show that the orfX-p47 cluster was not only present in the genomes of BoNT-producing bacteria but also in a substantially wider range of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…While the reference mapping settings utilized in our study allowed identification of protospacers with up to two mismatches and local alignment allowed some flexibility at the ends of the spacer-protospacer alignment, this approach is conservative compared with an 80% identity blastN threshold (Negahdaripour et al, 2017) and may have excluded more distant matches in other genera. Interestingly, nearly all matched plasmids were Gram-positive bacteria, and hits to plasmids in genera including Enterococcus and Paenibacillus are consistent with rare, but documented horizontal gene flows of bont gene cluster constituents (Zhang et al, 2018;Nowakowska et al, 2019). CRISPR-Cas system spacers will generally target MGEs that are most often encountered by the host strains (Shmakov et al, 2017), indicating that the plasmids present in the G1 C. botulinum and C. sporogenes mobilomes have been present long enough for CRISPR-CAS system mediated immunity to develop in certain strains.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…While the reference mapping settings utilized in our study allowed identification of protospacers with up to two mismatches and local alignment allowed some flexibility at the ends of the spacer-protospacer alignment, this approach is conservative compared with an 80% identity blastN threshold (Negahdaripour et al, 2017) and may have excluded more distant matches in other genera. Interestingly, nearly all matched plasmids were Gram-positive bacteria, and hits to plasmids in genera including Enterococcus and Paenibacillus are consistent with rare, but documented horizontal gene flows of bont gene cluster constituents (Zhang et al, 2018;Nowakowska et al, 2019). CRISPR-Cas system spacers will generally target MGEs that are most often encountered by the host strains (Shmakov et al, 2017), indicating that the plasmids present in the G1 C. botulinum and C. sporogenes mobilomes have been present long enough for CRISPR-CAS system mediated immunity to develop in certain strains.…”
Section: Discussionmentioning
confidence: 76%
“…Analysis of viral protospacers was limited to prophage present within closed G1 C. botulinum and C. sporogenes genomes, limiting insight into the broader host range targeted bacteriophage. However, matched RefSeq plasmids from other soil-dwelling Gram-positive genera included Paenibacillus and Enterococcus , which are known to possess genes homologous to bont gene cluster genes ( Zhang et al, 2018 ; Nowakowska et al, 2019 ). With further development, these data might enable enhanced risk assessment through the quantification of the normal range of horizontal gene transfer between G1 C. botulinum and other species.…”
Section: Resultsmentioning
confidence: 99%
“…Another intriguing finding showed that genes putatively encoding OrfX1–3 and P47 are found in genomes of a wide range of non‐BoNT‐producing bacterial species, such as Alphaproteobacteria , Bacilli , Betaproteobacteria , Cytophagia , and Gammaproteobacteria [44]. These orfX‐p47 ‐containing gene clusters show large diversity in their gene arrangement and gene content, and some are neighbouring genes encoding oral insecticidal toxins, such as delta‐endotoxins (Cry toxin), binary toxins (VIP toxin), or ABC toxins.…”
Section: Figmentioning
confidence: 99%
“…Type B neurotoxin genes are located on a small multicopy plasmid (47-63 kb) in a ha cluster that comprises genes encoding the neurotoxin, non-toxic-non-haemagglutinin (NTNH), three haemagglutinins, and a positive regulator (botR). Type E and F neurotoxin genes are generally located on the chromosome (but for a small fraction of strains, the type E neurotoxin gene is present on a single-copy plasmid) in an orfX cluster that comprises genes encoding the neurotoxin, NTNH, and four open reading frames of unknown function [3,16,17,[23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%